FUNCTIONAL COMPLIANCE OF THE PUBLIC ORGANIZATION AS A TARGETED OUTCOME OF PUBLIC MANAGEMENT INNOVATION - Tokar, M. (Pressing Problems of Public Administration, 2019)
It has been repeatedly stated in scientific circles that approaches that study or explain technological, economic or mathematical properties can be tested in practice in social science processes. When researching social phenomena and processes, comparing and adapting them to socio-political realities, we tend to support this view and, if possible, pragmatically introduce authors’ assumptions into scientific discourse. One of these innovations is the introduction into the practice of public life of citizens of managerial innovations, which in a timely manner change the approaches to understanding social changes and the use of new tactics and strategies of social and state development.The purpose of the article is to continue the search for optimization of the directions of the state policy for promoting the development of socially oriented public organizations in Ukraine and, in particular, the prerequisites and targeted implementation of institutional rebranding. We believe that this is not a formal end in itself of a renewed NGO and requires the use of managerial innovation. We emphasize the obligatory support of the mentioned process by the state, the policy of which should be built in the format of promoting and controlling the observance of the relevant norms and rules corresponding to the synergistic efforts of the state and civil society to successfully satisfy the social demands of citizens. In our opinion, the synergistic wave of unity of interests of the state and society, gives non-governmental organizations a specific social mission in the proposed direction, where functional compliance is a normalized process that has conscious prerequisites, progress and effectiveness. Its overall success depends on the mutual recognition of the specific rules, their observance in the process of cooperation and responsibility for a particular result and its subsequent consequences. The guarantee of such success lies in the continuous recruitment of skilled human resources, the use of their intellectual potential, the promotion of public activity and public administration, the improvement of the reputation of civil society through the introduction of managerial innovations, among which compliance management is considered to be one of the contemporary priorities of the community relations. The foregoing considerations bring to mind a new vision of the place and role of a socially useful public organization in the modern democratic culture of communication and significantly broaden the understanding of the essence of one of the key institutions of civil society.